Relations of Microvascular Function, Cardiovascular Disease Risk Factors, and Aortic Stiffness in Blacks: The Jackson Heart Study. Issue 20 (16th October 2018) - Cooper, Leroy L.; Musani, Solomon K.; Washington, Floyd; Moore, Jonathan; Tripathi, Avnish; Tsao, Connie W.; Hamburg, Naomi M.; Benjamin, Emelia J.; Vasan, Ramachandran S.; Mitchell, Gary F.; Fox, Ervin R.
Abstract : Background: Blacks have more severe endothelial dysfunction and aortic stiffening as compared with whites. We aimed to investigate the association between aortic stiffness and microvascular function in the black community. Methods and Results: We assessed the association between forearm vascular reactive hyperemia (an indicator of microvascular function) and aortic stiffness in 1458 black participants (N=965 [66% women]; mean age: 66±11 years) in the Jackson Heart Study. We evaluated 2 measures of aortic stiffness: brachial pulse pressure and carotid‐femoral pulse wave velocity. Using high‐resolution ultrasound and Doppler, we evaluated brachial blood flow at baseline and during reactive hyperemia after 5 minutes of forearm ischemia. Multiple cardiovascular risk factors were significantly related to baseline and hyperemic brachial flow velocity. Women had lower baseline flow across the entire age spectrum. During hyperemia, we observed a significant age‐sex interaction for flow velocity ( P =0.02). Female sex was protective against microvascular dysfunction among younger participants, but older women exhibited a greater attenuation of the hyperemic flow reserve. In multivariable models that adjusted for cardiovascular disease risk factors and mean arterial pressure, higher carotid‐femoral pulse wave velocity (β=−0.106±0.033; P =0.001 was related to lower baseline flow. However, during reactive hyperemia, elevated brachial pulse pressure (β=−0.070±0.031; P =0.03) and carotid‐femoral pulse wave velocity (β=−0.128±0.030; P <0.001) were both related to attenuated brachial flow velocity. Conclusions: In a sample of blacks, higher aortic stiffness and pressure pulsatility were associated with lower flow reserve during reactive hyperemia, beyond changes attributable to traditional cardiovascular disease risk factors alone.